Performance of highly sensitive cardiac troponin T assay to detect ischaemia at PET-CT in low-risk patients with acute coronary syndrome: a prospective observational study. Issue 7 (10th July 2017) - Morawiec, Beata; Fournier, Stephane; Tapponnier, Maxime; Prior, John O; Monney, Pierre; Dunet, Vincent; Lauriers, Nathalie; Recordon, Frederique; Trana, Catalina; Iglesias, Juan-Fernando; Kawecki, Damian; Boulat, Olivier; et al.
Abstract : Background: Highly sensitive troponin T (hs-TnT) assay has improved clinical decision-making for patients admitted with chest pain. However, this assay's performance in detecting myocardial ischaemia in a lowrisk population has been poorly documented. Purpose: To assess hs-TnT assay's performance to detect myocardial ischaemia at positron emission tomography/CT (PET-CT) in low-risk patients admitted with chest pain. Methods: Patients admitted for chest pain with a nonconclusive ECG and negative standard cardiac troponin T results at admission and after 6 hours were prospectively enrolled. Their hs-TnT samples were at T0, T2 and T6. Physicians were blinded to hs-TnT results. All patients underwent a PET-CT at rest and during adenosine-induced stress. All patients with a positive PET-CT result underwent a coronary angiography. Results: Forty-eight patients were included. Six had ischaemia at PET-CT. All of them had ≥1 significant stenosis at coronary angiography. Areas under the curve (95% CI) for predicting significant ischaemia at PET-CT using hs-TnT were 0.764 (0.515 to 1.000) at T0, 0.812(0.616 to 1.000) at T2 and 0.813(0.638 to 0.989) at T6. The receiver operating characteristicbased optimal cut-off value for hs-TnT at T0, T2 and T6 needed to exclude significant ischaemia at PET-CT was <4 ng/L. Using this value, sensitivity, specificity, positive and negative predictive values of hs-TnT to predict significant ischaemia were 83%/38%/16%/94% at T0, 100%/40%/19%/100% at T2 and 100%/43%/20%/100% at T6, respectively. Conclusions: Our findings suggest that in low-risk patients, using the hs-TnT assay with a cut-off value of 4 ng/L demonstrates excellent negative predictive value to exclude myocardial ischaemia detection at PET-CT, at the expense of weak specificity and positive predictive value. Trial registration number: ClinicalTrials.gov Identifier: NCT01374607 .